The immediate effects of blood flow restriction training on upper limb muscle strength and fatigue level: a meta-analysis - Wang, J.; Xu, J.; Liu, H.; Jiang, L. (Frontiers in Physiology, 2025)
Objective: Blood flow restriction training (BFR training) has gained recognition as a potentially effective intervention; however, its specific effects on upper limb strength and fatigue levels remain inadequately explored. This study aims to systematically assess the impact of BFR training on immediate upper limb strength and fatigue through a meta-analytic approach, with the goal of providing empirical evidence to inform its practical implementation in clinical and athletic settings.